Analysis of the primary drying stage of a one-dimensional freeze-drying model with moving boundary - Dimalanta, Theresa Lina Borja
The system of partial differential equations modeling the primary drying stage of the freeze-drying process is derived and analyzed. We first derive the equations modeling the temperature in the freeze-dried region, the temperature in the frozen region, the concentration of sorbed water in the freeze-dried region, and the partial pressure of sorbed water in the freeze dried region.